Advanced processing and simulation of MRS data using the FID appliance (FID‐A)—An open source, MATLAB‐based toolkit. Issue 1 (30th December 2015) - Simpson, Robin; Devenyi, Gabriel A.; Jezzard, Peter; Hennessy, T. Jay; Near, Jamie
Abstract : Purpose: To introduce a new toolkit for simulation and processing of magnetic resonance spectroscopy (MRS) data, and to demonstrate some of its novel features. Methods: The FID appliance (FID‐A) is an open‐source, MATLAB‐based software toolkit for simulation and processing of MRS data. The software is designed specifically for processing data with multiple dimensions (eg, multiple radiofrequency channels, averages, spectral editing dimensions). It is equipped with functions for importing data in the formats of most major MRI vendors (eg, Siemens, Philips, GE, Agilent) and for exporting data into the formats of several common processing software packages (eg, LCModel, jMRUI, Tarquin). This paper introduces the FID‐A software toolkit and uses examples to demonstrate its novel features, namely 1) the use of a spectral registration algorithm to carry out useful processing routines automatically, 2) automatic detection and removal of motion‐corrupted scans, and 3) the ability to perform several major aspects of the MRS computational workflow from a single piece of software. This latter feature is illustrated through both high‐level processing of in vivo GABA‐edited MEGA‐PRESS MRS data, as well as detailed quantum mechanical simulations to generate an accurate LCModel basis set for analysis of the same data. Results: All of the described processing steps resulted in a marked improvement in spectral quality compared with unprocessed data. Fitting of MEGA‐PRESS data using a customized basis set resulted in improved fitting accuracy compared with a generic MEGA‐PRESS basis set. Conclusions: The FID‐A software toolkit enables high‐level processing of MRS data and accurate simulation of in vivo MRS experiments. Magn Reson Med 77:23–33, 2017. © 2015 Wiley Periodicals, Inc.